Implant Survival of an Uncemented Modular Femoral Implant in Patients With Severe Femoral Bone Loss and 2-Stage Hip Revision - Sebastian Winther; Naima Elsayed; Karen Dyreborg; Elinborg Mortensen; Michael. M. Petersen; Jens Stürup; Nikolaj S. Winther (Advances in Orthopedics)
Conclusion: In complex cases of revision THA, using a modular revision femoral system yielded promising results. The 5-year implant survival estimated by Kaplan–Meier survival analysis was 95% (95%-CI: 91%–99%), with all hips demonstrating radiographic evidence of osseointegration and no one with subsidence greater than 5 mm. Notably 80% showed radiographic evidence of restoration of proximal femoral bone.